Using geographic profiling to locate elusive nocturnal animals: a case study with spectral tarsiers. (22nd January 2015) - Faulkner, S. C.; Stevenson, M. D.; Verity, R.; Mustari, A. H.; Semple, S.; Tosh, D. G.; Le Comber, S. C.
Abstract: Estimates of biodiversity, population size, population density and habitat use have important implications for management of both species and habitats, yet are based on census data that can be extremely difficult to collect. Traditional assessment techniques are often limited by time and money and by the difficulties of working in certain habitats, and species become more difficult to find as population size decreases. Particular difficulties arise when studying elusive species with cryptic behaviours. Here, we show how geographic profiling (GP) – a statistical tool originally developed in criminology to prioritize large lists of suspects in cases of serial crime – can be used to address these problems. We ask whether GP can be used to locate sleeping sites of spectral tarsiers T arsius tarsier in Sulawesi, Southeast Asia, using as input the positions at which tarsier vocalizations were recorded in the field. This novel application of GP is potentially of value as tarsiers are cryptic and nocturnal and can easily be overlooked in habitat assessments (e.g. in dense rainforest). Our results show that GP provides a useful tool for locating sleeping sites of this species, and indeed analysis of a preliminary dataset during field work strongly suggested the presence of a sleeping tree at a previously unknown location; two sleeping trees were subsequently found within 5 m of the predicted site. We believe that GP can be successfully applied to locating the nests, dens or roosts of elusive animals such as tarsiers, potentially improving estimates of population size with important implications for management of both species and habitats.